Faktor yang berhubungan dengan frekuensi penimbangan balita di posyandu - Ariyani, Rina Dwi; Susanti, Rini; Mardiyaningsih, Eko (Jurnal Keperawatan Soedirman, 2012)
Integrated Services Pos is a program of the Government of Indonesia which is useful for monitoring the growth and development of children under five every month. This study aims to determine the factors associated with the frequency of infants weighing. Design of the study is a descriptive study of correlation with cross-sectional approach. The population in this study were mothers of young children in the Pilangrejo village Integrated Services Pos. Sample in this study using purposive sampling techniques to obtain 74 samples. According to the results of research in getting the p value 0.003, so is rejected it means no employment relationship with the frequency of weighing a toddler. There is a relationship of maternal knowledge with the frequency of weighing infants with p value 0,000. Health centers are expected to further improve infrastructure facilities in Integrated Services Pos is to provide a better weighing equipment and provide a schedule Integrated Services Pos in the afternoon so that working mothers so that people can follow the activities of Integrated Services Pos.Ã‚Â